2023
DOI: 10.3390/ma16134539
|View full text |Cite
|
Sign up to set email alerts
|

1D Narrow-Bandgap Tin Oxide Materials: Systematic High-Resolution TEM and Raman Analysis

Kazuhiro Manseki,
Saeid Vafaei,
Loren Scott
et al.

Abstract: We demonstrate for the first time the structure identification and narrow-bandgap property of 1D hybridized SnO/SnO2 nanoparticles derived from the calcination of a single-source precursor, i.e., tin(II) oxalate. Systematic Raman analysis together with high-resolution TEM (HR-TEM) measurements of the tin oxide samples were carried out by changing the calcination temperatures. These data revealed the simultaneous formation of 1D SnO/SnO2 in the rod particles that grew in air. It was also found that Sn(II) can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…These low-dimensional-structures can be tied into pillars and other geometrically organized macrostructures [15]. Manseki et al [16] presented an example of the structure recognition and narrow-bandgap properties of assembled SnO/SnO 2 nanoparticles, as derived from the thermal treatment in air of Tin(II) oxalate. The authors observed the simultaneous formation of SnO/SnO 2 nanoparticles with sizes of 20-30 nm arranged into nanostructured rods, as obtained during the heating step (350-600 • C range).…”
Section: The Special Issuementioning
confidence: 99%
“…These low-dimensional-structures can be tied into pillars and other geometrically organized macrostructures [15]. Manseki et al [16] presented an example of the structure recognition and narrow-bandgap properties of assembled SnO/SnO 2 nanoparticles, as derived from the thermal treatment in air of Tin(II) oxalate. The authors observed the simultaneous formation of SnO/SnO 2 nanoparticles with sizes of 20-30 nm arranged into nanostructured rods, as obtained during the heating step (350-600 • C range).…”
Section: The Special Issuementioning
confidence: 99%